Dirt of Art in Madame Bovary - Yeasmin, Nellufar (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Flaubert’s Madame Bovary is a unique literary piece that incorporates aestheticism and witty disposure to Emma’s complex reality. The pronounced acceptance and reputation of the novel despite of a prolonged period of criticism proves that the universal appeal of this French novel lies in the artistic and tactful disclosure (in precisely calculative and measured style) of the dark secrets of a feminine mind. The fact that the English translation of this ingenious creation is so influential attests the superiority of its quality in French. The splendor of the narration overreaches the boundaries of life, experience and death and abounds in the exaltation of becoming a masterpiece. This article illustrates the features that make the manuscript so overwhelmingly “dirty” yet inviting. In course of appreciating the novel, the prospects of readers’ fascination and the author’s intentions are also evaluated from the archive of appreciations of the book. The richness of the story is imparted by the pragmatic effect of the objective correlatives in Falubert’s style and the details of the emotional intensities. This study urges to dismantle the complicated value of literature in realizing life. It also reinforces the poetic justice to prevail where art must exist for its sole sake. Emma, the centre of interest in Madame Bovary, is the ambassador of human beings who fail to achieve the mused state of their existence. Flaubert with his strokes of wisdom and dexterous artistic maneuver reveals the ultimate paradox of anarchy in the social conventions designed to annihilate the self in order to discover it. This study unfolds how the story of shame and guilt turns into an allegory of life by the writer’s magic wand.